ANALISIS KEBIJAKAN PENINGKATAN PENGHASILAN GURU DALAM UPAYA MENURUNKAN TURNOVER DI YAYASAN PERGURUAN AL-FATTAH MEDAN - Ika Desni Sarwesti; Zahari Zein; Iskandarini iskandarini (Universitas Islam Negeri Sumatera Utara Medan, 2016)
Teachers are human resources that educators have an important function in therole agents of change to create a social and cultural changes in society. Al- FattahEducation Foundation Medan as one of the educational institutions to develop themselvesto improve the quality of human resources through activities that lead to the abilitythemselves to mastery of Science Technology (Science and Technology), which remainsgrounded to religious values with Islamic nuance. Each year the Education Foundationof Al-Fattah Medan had a problem with high turnover in teachers. In order for a highturnover rate can be resolved, then the organization Al-Fattah Education FoundationTerrain should establish policies that can make teachers managed to survive in theorganization. The purpose of this paper to determine the income of teachers to analyzethe relationship between turnover, to analyze the influence of organizational culture,leadership style, job satisfaction, compensation, and career on Turnover, and todetermine policies to raise money for a teacher in Al-Fattah Education FoundationMedan. The results obtained from this author suggests that the variable income (salary)consists of a sub-variable amount of salary (X1), Regulation Payroll (X2), and PrecisionTime Payroll (X3) influence Turnover in Education Foundation Al-Fattah Medan eitherpartially or simultaneously. Salary large amount of ability, Regulation Payroll andPayroll Timeliness teacher explains Turnover amounted to 82.4% while the remaining17.6%. Further variables Internal factors Turnover ie sub-variables CulturalOrganization (X1), Leadership Style (X2), job satisfaction (X3), Compensation (X4), andCareer (X5) affects Turnover Master in Education Foundation Al-Fattah Medan eitherpartially or simultaneously. Great ability Organizational Culture, Leadership Style, JobSatisfaction, Compensation, and Careers teacher explains Turnover amounted to 75.4%while the remaining 24.6% is explained by other variables not included in this study.Keywords: Turnover, Yayasan Perguruan Al-Fattah Medan, Penghasilan Guru